Influência de Bacillus spp. na promoção de crescimento de plantas de arroz - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The state of Rio Grande do Sul is the largest national producer of rice, however, in recent years there has been a significant increase in production costs, requiring producers to look for alternatives to maintain productivity without increasing product costs. One of these alternatives is the use of biological products, which increase the efficiency of plants in using available resources, can promote growth and protect against disease, lowering costs with fertilizers and chemicals. Thus, the objective of this study was to evaluate the effect of biological products produced with bacteria of the genus Bacillus on the growth promotion of rice plants in vitro and in a greenhouse. The experiment consisted of treating rice seeds of cultivar GURI INTA CL with four biological products produced with bacteria of the genus Bacillus and a control. In the in vitro test, shoot length, root length, fresh and dry weight of shoot and weight of fresh and dry root were evaluated. In the greenhouse test, root length, plant height, shoot fresh and dry matter, root fresh and dry matter and leaf number were evaluated. The treatment with B. amyloliquefaciens and unformulated B. methylotrophicus were the most effective in the in vitro test. In a greenhouse, all treatments were effective in increasing plant height, and the treatment with B. methylotrophicus was the most effective for the variables shoot and root fresh matter, shoot and root dry matter and number of leaves, although it does not differ from the control. From the results obtained in this study, it is possible to verify that the biological products tested, produced based on bacteria of the genus Bacillus, have potential to promote growth in rice plants, because they were able to promote increments in practically all evaluated characters.
Keywords: Oryza sativa; Bactérias benéficas; Agricultura sustentável; Beneficial bacteria; Sustainable agriculture; B. amyloliquefaciens; B. methylotrophicus; CNPQ::CIENCIAS AGRARIAS